Aspiration of superabsorbent polymer beads resulting in focal lung damage: a case report - Nasser Alharbi; Maryam Dabbour (BMC, 2020)
Abstract Background Concerns have recently been raised about reported incidents of intestinal obstruction following ingestion of Superabsorbent polymer (SAP) beads. Texas Poison Centers reported 110 cases of superabsorbent polymer bead ingestions between 2011 and 2016 (Pediatr Emerg Care 35:426-7, 2019). Furthermore, cases of related auditory complications following the placement of SAP beads into the external auditory canal have also been reported. Here, we report the first case of significant airway damage secondary to the ingestion of a SAP bead (Orbeez), which was aspirated and then overlooked. Further, we hypothesized that the capability of the bead to expand in size once exposed to water from the respiratory mucous may contribute to airway damage. Case presentation A 3-year-old boy presented to our hospital with persistent cough and recurrent hospitalizations to the general ward and intensive care unit. The boy was diagnosed with focal lung bronchiectasis in the left lower lobe, which occurred after the patient aspirated an Orbeez bead before a year. The bead was removed using flexible bronchoscopy and a retrieval basket. Conclusion Orbeez beads are commonly ingested by young children resulting in gastrointestinal obstruction. The beads can easily be aspirated by children and overlooked by their caregivers and physicians for long periods of time due to their small size. The bead can cause significant airway damage after multiplying in size when coming into contact with respiratory mucus which consists of 95% water.